The Mediating Role of Capital Structure in the Impact of Profitability and Liquidity on Firm Value - Dwi Puji Astuti; Bambang Mahmudi; Ana Susi Mulyani (Indonesian Journal of Innovation Multidisipliner Research, 2024)
Companies in the property and real estate sectors play a significant role in the economic growth of a country because they are among the sectors that contribute the most to investment realisation in Indonesia. A company's worth is a key indicator of its performance for businesses in the real estate and property industries. The purpose of this study is to determine how profitability and liquidity affect a company's value by using capital structure as an intervening variable. The study will focus on real estate and property sector businesses that are listed on the Indonesian Stock Exchange between 2013 and 2022. Purposive sampling is used in the study, and a sample of 14 samples from 43 property and real estate businesses are used. In this study, the application of SPSS 25 is used as a data analysis tool that will be described with descriptive statistical methods and inferential statistics. The results of the research, obtained in part, show that profitability and capital structure have a significant positive impact on the value of the company. Liquidity has a significant negative impact on company value. Profitability and liquidity have significant negative effects on capital structure. Capital structure is unable to mediate the impact of profitability on the company's value but mediates the effect of profitability on firm value.